2020
DOI: 10.22581/muet1982.2001.15
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Based Approach for Improving Outpatient Clinic Operations

Abstract: The aim of this study is to suggest the optimum number and schedule of doctors at the OPD (Out-Patient Department) of Gastrology of a hospital in Pakistan. In order to achieve this aim, the discrete event simulation model is developed to minimize waiting time of patients. Data is collected for one week from the OPD; Data collection variables are arrival and service rate of patients, their salaries/income, patient‘s OPD fee, doctor’s charges/patient, service time of patients at each of service channel i.e. rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Because of manual reporting in excel, a lot of time was used to be spent on the formation of reports and the purchase department used to decide for the vendors` performance. Since, cost is associated with the time (Kalwar, Khaskheli, Khan, Siddiqui, & Gopang, 2018;Kalwar, Mari, Memon, Tanwari, & Siddiqui, 2020;Khaskheli et al, 2020) and decisions were based on the report and at the same time, chance of errors in the report was greater; thus it was decided to automate the material delivery time analysis report. New method/suggested method is consisted of interface (userform) designed to execute the various macros for performing the tasks automatically in MS excel.…”
Section: Suggested Methods For Making the Reportmentioning
confidence: 99%
“…Because of manual reporting in excel, a lot of time was used to be spent on the formation of reports and the purchase department used to decide for the vendors` performance. Since, cost is associated with the time (Kalwar, Khaskheli, Khan, Siddiqui, & Gopang, 2018;Kalwar, Mari, Memon, Tanwari, & Siddiqui, 2020;Khaskheli et al, 2020) and decisions were based on the report and at the same time, chance of errors in the report was greater; thus it was decided to automate the material delivery time analysis report. New method/suggested method is consisted of interface (userform) designed to execute the various macros for performing the tasks automatically in MS excel.…”
Section: Suggested Methods For Making the Reportmentioning
confidence: 99%
“…Kritchanchai and Hoeur [ 45 ] built two DES models of old and new OPD to compare its performance and the result showed that if the healthcare changes the allocation of facilities as in the new OPD, the congestion in floor area can be reduced. Kalwar et al [ 46 ] used DES to help in finding the optimal number of doctors in OPD by applying scenario analysis. Moreover, DES can be integrated with other techniques to improve the model performance.…”
Section: Related Workmentioning
confidence: 99%
“…Aeenparast et al (2019) concluded that physician delay was a major factor in increased outpatient wait times in a general hospital in Iran. In a recent study in Pakistan, Kalwar et al . (2020) evaluated the wait times within a gastrology department for patients with appointments suggesting that doctors should sit in for longer hours.…”
Section: Introductionmentioning
confidence: 99%
“…Aeenparast et al, (2019) concluded that physician delay was a major factor in increased outpatient wait times in a General hospital in Iran. In a recent study in Pakistan, Kalwar et al, (2020) evaluated the wait times within a Gastronlogy department for patients with appointments suggesting that doctors should sit in for longer hours. Although these suggestions are reasonable, but not currently implementable as almost all public hospitals of developing economies are highly unorganised, overcrowded, and all patients are walk-in with variable arrival pattern.…”
Section: Introductionmentioning
confidence: 99%